2005
DOI: 10.1677/jme.1.01730
|View full text |Cite
|
Sign up to set email alerts
|

The secretin G-protein-coupled receptor family: teleost receptors

Abstract: Twenty-one members of the secretin family (family 2) of G-protein-coupled receptors (GPCRs) were identified via directed cloning and data-mining of the Fugu Genome Consortium database, representing the most comprehensive description of secretin GPCRs in a teleost fish to date. Duplicated genes were identified for many of the family members, namely the receptors for pituitary adenylate cyclase-activating polypeptide (PACAP)/vasoactive intestinal peptide (VIP), calcitonin, calcitonin gene-related peptide (CGRP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 64 publications
3
35
0
Order By: Relevance
“…Similar to bgPRP in in vitro assays, a sex-dependent effect of fGHRH on bFSH and GH gene expression was demonstrated in this study, probably because the receptors are structurally related (Cardoso et al 2005). Functional assays revealed that the PRP receptors in both zebrafish and goldfish are most sensitive to one of their PRP, but both also bind GHRH ).…”
Section: Discussionsupporting
confidence: 72%
“…Similar to bgPRP in in vitro assays, a sex-dependent effect of fGHRH on bFSH and GH gene expression was demonstrated in this study, probably because the receptors are structurally related (Cardoso et al 2005). Functional assays revealed that the PRP receptors in both zebrafish and goldfish are most sensitive to one of their PRP, but both also bind GHRH ).…”
Section: Discussionsupporting
confidence: 72%
“…Third, in NJ and ML phylogenetic trees, fugu VPAC2RA and VPAC2RB cluster more closely with zebrafish PHIR than with chicken and human VPAC2R. However, the sequence similarity may not represent functional equivalence as addressed by Cardoso et al (2005). Whether fugu VPAC2RA and VPAC2RB are PHI receptors will be defined by functional assays.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining three genes each encode only a single hormone: growth hormone-releasing hormone (GHRH), secretin (SCT), or glucose-dependent insulinotropic polypeptide (GIP). The nine receptors that bind these hormones are also structurally related as seven transmembrane receptors, which are grouped within the type B (or type 2) family of G-proteincoupled receptors , Ulloa-Aguirre & Conn 2000, Cardoso et al 2005 and named by the International Union of Pharmacology (Foord et al 2005). An understanding of the evolutionary history of the secretin superfamily of hormones and receptors may help to explain the gene organization, receptor binding, and function of this group of hormones.…”
Section: Introductionmentioning
confidence: 99%
“…In frog, however, VPAC1-R is able to bind both VIP and PACAP (Alexandre et al, 2000a), suggesting that the receptor ability to interact with PACAP could have emerged only after the divergence giving rise to the tetrapod lineage. In fact, based on gene prediction of the class II B receptor family in teleosts, it has been proposed that the VPAC1-R gene is the ancestral form of the receptor (Cardoso et al, 2005). Thus, the first VIP/PACAP receptor possibly interacted specifically with VIP but not with PACAP.…”
Section: Phylogenetic Evolution Of Pituitary Adenylate Cyclase-actmentioning
confidence: 99%